Texture development and surface reconstruction of BiVO4 photoanode via one-pot hydrothermal reaction for enhanced photoelectrochemical water splitting - Sung Won Hwang; Yoo Jae Jeong; Runfa Tan; Indhujasri Saravanan; Hyun Soo Han; Dong Hoe Kim; In Sun Cho (Journal of Advanced Ceramics)
The simultaneous optimization of the bulk and surface characteristics of photoelectrodes is essential to maximize their photoelectrochemical (PEC) performance. We report a novel one-pot hydrothermal synthesis of textured and surface-reconstructed BiVO4 photoanodes (ts-BVO), achieving significant improvements in PEC water splitting. By controlling precursor molarity and ethylene glycol (EG) addition, we developed a stepwise dual reaction (SDR) mechanism, which enables simultaneous bulk texture development and surface reconstruction. The optimized CoBi/ts-BVO photoanode exhibited a photocurrent density of 4.3 mA∙cm−2 at 1.23 V vs. reversible hydrogen electrode (RHE) with a high Faradaic efficiency of 98% under one sun illumination. Compared with nontextured BiVO4, the charge transport efficiency increased from 8% to 70%, whereas the surface charge transfer efficiency improved from 9% to 85%. These results underscore the critical role of both bulk and surface engineering in enhancing PEC performance. Our findings offer a streamlined approach for improving the intrinsic properties of photoanodes in solar water splitting.